Estudio de la felicidad en los trabajadores del Gobierno Autónomo Descentralizado Municipal del cantón Latacunga. - Moreira Bailón, Fernanda Elizabeth (2023)
Institutions constantly seek to improve the performance and well-being of employees, the topic of happiness is a recent area of study, in order to measure worker satisfaction and apply strategies that are reflected in optimal performance not only of the worker but also of the institution. The objective of this investigative work is to determine the existing relationship between work and happiness of the workers of the Municipal Decentralized Autonomous Government of the Latacunga canton, through the application of the Chamba 1.0 Index, determining the percentage of life satisfaction and job satisfaction, finding factors that provide greater or lesser happiness to the worker. This research followed a deductive methodology, framed in a quantitative approach based on data collection through the survey technique, applying the Chamba Index 1.0 instrument, analyzing the data through two scales: We work to live and Chamba. It is work, applied to a sample population of 280 workers with a labor code regime. The results obtained indicate that there is a relationship between work and the happiness of workers, showing dissatisfaction in the worker, so the expectation is greater than the achievement. Allowing us to identify and propose measures that increase the percentage of worker satisfaction, achieving greater performance and productivity, as well as being a reference guide for future research regarding the study of happiness in the workplace, specifically in the public sector at a national level.